The Influence Of Electronic Word Of Mouth and Perceived Value on Online Purchasing Decisions Purchasing Decisions on the Shopee Marketplace - Bela Dania Putri; Irsandi, Irsandi; Trenggono Pujo Sakti (International Journal of Economics, Business and Innovation Research, 2025)
This research aims to test and analyze the influence of Electronic Word of Mouth and Perceived Value on Online Purchasing Decisions. This research was conducted on the Shopee Marketplace, a case study of Bandar Lampung University students. The sample for this research consisted of 65 respondents using random sampling techniques. Data were analyzed using multiple linear regression analysis, classical assumption test, T test, and coefficient of determination using SPSS software. The research results prove that partially there is a significant influence of the Electronic Word of Mouth variable on Online Purchasing Decisions, the Perceived Value variable has a significant impact on Online Purchasing Decisions.